Preservation Effect of Different Freezing Treatment on the Braised Beef Prefabricated Dishes - Zhu, Yongjie; Zhu, He; Xing, Yanxia (International Journal of Agriculture and Food Sciences Research, 2024)
This thesis takes the braised beef meal kit as the experimental object, selects two freezing methods of refrigerator (-18℃) and liquid frozen sleep (-25℃) for processing and then stores it in the refrigerator (-18℃) for 30 days, aiming to study the preservation effect of liquid frozen sleep technology on prefabricated dishes under frozen storage conditions. Taking cold storage (4℃) as the blank, the changes of texture, color, water content, sensory quality, protein structure and volatile components of braised beef were determined on the 10th, 20th and 30th days. The main research conclusions are as follows: In terms of texture, the hardness, chewiness and elasticity of beef all show a downward trend during storage, and the range of the frozen sleep group is lower than that of the refrigerator group; in terms of color, the L* value shows a trend of first increasing and then decreasing during storage, and the a* and b* values show a downward trend, among which the changes of the frozen sleep group are all smaller than those of the refrigerator group; in terms of water content, the water content of beef in the refrigerator group decreased from 67% to 50%, and the water content of beef in the frozen sleep group decreased from 67% to 56%; in terms of the secondary structure of protein, with the extension of storage time, the hydrogen bonds of the highly ordered α-helix structure are broken, and gradually transformed to the disordered β-turn and random coil structure, while the contents of the regular and ordered structures of α-helix and β-fold in the frozen sleep group decrease less than those in the refrigerator group; in terms of volatile components, the content of volatile substances of both freezing methods increases with the extension of storage time, while the content of volatile substance components of the frozen sleep group increases less. Liquid frozen sleep technology can be applied to the storage of braised beef, which can make the meat products maintain better quality in prefabricated dishes.